SOCIAL PREMISES FOR A SUSTAINABLE LEATHER INDUSTRY - Trandafir Nicoleta; Cismas Laura; Pinteala Gheorghe (Annals of the University of Oradea: Economic Science, 2014)
Sustainability is not any more a new and un-known subject in the leather business world. There is a certain reorientation and implementation tendency of its requirements at organization level, in the last years. However, there are still some ambiguities and uncertainties related on the approach and practice of all principles included in the concept. That’s why each organization tries to formulate winning strategies on long term, showing an equal importance for human resources, social balance and the environment. This work highlights the efficiency of the human resources in the leather industry’s sustainability, a study created by seven national associations representing the leather industry from Italy, Spain, France, Germany, UK, Sweden and Romania. The analysis of social indicators demonstrates that tanneries in Europe are increasingly committed to the ethical and social aspects of their business, and that, through continuous investments, they have been able to ensure substantial improvements in process efficiency and in pollution prevention and control. All the efforts made by European tanneries over the years have resulted in improving the sustainability of their production. The excellent results achieved deserve to be valued more by stakeholders and better incentivised through measures encouraging new and future investments. The environmental and social values demonstrated by European leather help to keep European tanners ahead of international competition.